Collteral loop approach from left to right liver lobe: Endovascular recanalization of a hepatic vein in Budd-Chiari syndrome - Pereira da Silva, F (2016)
We report the approach to a 29 year old patient presenting with the diagnosis of a Budd-Chiari Syndrome, with clinical deterioration after initial anticoagulation treatment. The patient was proposed to endovascular treatment. Through intra-hepatic shunting seen at angiography, and from a left to right liver lobe, a guide-wire was passed retrogadely and allowed sufficient support to perform hepatic vein angioplasty and stenting. The patient responded favourably and liver transplant was avoided.